The Urgency of Peace Education in Aceh's Educational Institutions - Halik Halik; Siti Ikramatoun; Nina Suryana (Jurnal Sosiologi Agama Indonesia (JSAI), 2023)
The protracted conflict in Aceh has inflicted significant damage upon the region's social and educational infrastructure, engendering an urgent imperative for the integration of peace education within educational institutions. This article aims to discuss the urgency of peace education in Aceh's educational institutions. A qualitative research methodology, employing a literature study approach, was adopted, gathering and analyzing data from various relevant sources to gain a comprehensive understanding. This study showed that peace education is not only critical for post-conflict recovery but also essential in shaping the attitudes of tolerance and conflict understanding among the youth. This need is underscored by Aceh's conflict history and its enduring impact on society. The article concludes that peace education is an urgent requirement in Aceh's schools, with the potential to equip students with knowledge and attitudes supportive of sustained peace and future violence prevention. Investment in peace education in Aceh is vital for regional stability and serves as a potential global model for post-conflict peacebuilding.